Synthesis and Electrochemical Performance of ZnSe Electrospinning Nanofibers as an Anode Material for Lithium Ion and Sodium Ion Batteries - Zhou, Peng; Zhang, Mingyu; Wang, Liping; Huang, Qizhong; Su, Zhean; Li, Liewu; Wang, Xiaodong; Li, Yuhao; Zeng, Chen; Guo, Zhenghao (Frontiers in Chemistry, 2019)
ZnSe nitrogen-doped carbon composite nanofibers (ZnSe@N-CNFs) were derived as anode materials from selenization of electrospinning nanofibers. Electron microscopy shows that ZnSe nanoparticles are distributed in electrospinning nanofibers after selenization. Electrochemistry tests were carried out and the results show the one-dimensional carbon composite nanofibers reveal a great structural stability and electrochemistry performance by the enhanced synergistic effect with ZnSe. Even at a current density of 2 A g-1, the as-prepared electrodes can still reach up to 701.7 mA h g-1 after 600 cycles in lithium-ion batteries and 368.9 mA h g-1 after 200 cycles in sodium-ion batteries, respectively. ZnSe@N-CNFs with long cycle life and high capacity at high current density implies its promising future for the next generation application of energy storage.